2014
DOI: 10.1016/j.ijdevneu.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of Hes5 protein in Notch signaling pathway in the hippocampus of mice offspring of dams fed a high‐fat diet during pregnancy and suckling

Abstract: Maternal high-fat diet (HFD) impairs hippocampal development of offspring promoting decreased proliferation of neural progenitors, in neuronal differentiation, in dendritic spine density and synaptic plasticity reducing neurogenic capacity. Notch signaling pathway participates in molecular mechanisms of the neurogenesis. The activation of Notch signaling leads to the upregulation of Hes5, which inhibits the proliferation and differentiation of neural progenitors. This study aimed to investigate the Notch/Hes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Moreover, consistent with previous studies (Molteni et al 2002, Wu et al 2004, we also found that HFD consumption in adulthood decreases the hippocampal BDNF levels. Additionally, maternal HFD has also been demonstrated to impair hippocampal development of offspring, promoting decreased neuronal differentiation, and Notch 1 signaling in this brain region may be involved in the process (Mendes-da-Silva et al 2015). Glucocorticoid exposure is a critical determinant of stroke outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, consistent with previous studies (Molteni et al 2002, Wu et al 2004, we also found that HFD consumption in adulthood decreases the hippocampal BDNF levels. Additionally, maternal HFD has also been demonstrated to impair hippocampal development of offspring, promoting decreased neuronal differentiation, and Notch 1 signaling in this brain region may be involved in the process (Mendes-da-Silva et al 2015). Glucocorticoid exposure is a critical determinant of stroke outcome.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most vulnerable brain areas affected by HFD is the hippocampus, resulting in a delayed utero development [5], learning and memory impairment, and addiction-like behaviors [6]. The mechanisms involved are exacerbated proliferation of astrocytes, increased stress response to acute stimuli [7], and altered development of the placental vasculature [8].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, leptin is a main player known to be involved in the regulation of body weight and energy balance by acting as a hunger suppressant signal to the brain (Hamed et al, 2011). According to a recent experimental study maternal HFD might also result in hippocampal inflammation with several consequences on the offspring, given the pivotal role played by the hippocampus in several cognitive processes, in addition to emotional behavior (Mendes-da-Silva et al, 2015).…”
Section: Introductionmentioning
confidence: 99%